Spatiotemporal Dynamics of Microplastics in Nakivubo Catchment: Implications for the Pollution of Lake Victoria - Simon Ocakacon; Philip Mayanja Nyenje; Herbert Mpagi Kalibbala; Robinah Nakawunde Kulabako; Christine Betty Nagawa; Timothy Omara; Christine Kyarimpa; Solomon Omwoma Lugasi; Patrick Ssebugere (Microplastics)
Microplastics (MPs) have been extensively studied in the marine environment, but reliable data on their sources and pathways in freshwater ecosystems, which are the main sources of such pollutants, are still limited. In this study, we investigated the spatiotemporal variations, characteristics, and sources of MPs in Nakivubo catchment, which drains waste and stormwater from Kampala city (Uganda) and empties it into Lake Victoria through the Nakivubo channel. Surface water samples (n = 117) were collected from thirteen sites in the Nakivubo catchment (S1 to S13) during the dry and wet seasons in 2022. The MPs were recovered by wet peroxide oxidation protocol, followed by salinity-based density separation, stereomicroscopy, and micro-attenuated total reflectance Fourier-transform infrared spectroscopy. All the samples had MPs, with mean concentrations ranging from 1568.6 ± 1473.8 particles/m3 during the dry season to 2140.4 ± 3670.1 particles/m3 in the wet season. Nakivubo catchment discharges an estimated 293.957 million particles/day into Lake Victoria. A Two-Way ANOVA revealed significant interactive effects of seasons and sampling sites on MPs abundance (p < 0.05). Spatially, the highest mean concentrations of MPs (5466.67 ± 6441.70 particles/m3) were in samples from site S3, which is characterized by poor solid waste and wastewater management practices. Filaments (79.7%) and fragments (17.9%) made of polyethylene (75.4%) and polyethylene/polypropylene co-polymer (16.0%) were the most common MPs. These are likely from single-use polyethylene and polypropylene packaging bags, water bottles, and filaments shed from textiles during washing. These results highlight the ubiquity of MPs in urban drainage systems feeding into Lake Victoria. To mitigate this pollution, urban authorities need to implement strict waste management policies to prevent plastic debris from entering drainage networks.